JAMES JOYCE’S “ULYSSES”: READING THE SELF IN THE BODY - Vlad MELNIC (Studia Universitatis Babeş-Bolyai. Philologia, 2018)
James Joyce’s “Ulysses”: Reading the Self in the Body. Throughout this paper, my primary contention is that, as a book, Ulysses is a body of potentialities meant to help readers consubstantiate with their selves, with a special dedication for the Irish audience of the 1900s in particular. I suggest, in other words, that from a post-humanist perspective, the novel’s most metempsychotic feature remains its ability to guide readers out of their self-legitimising narratives and into the seat of their consciousness, the individual body. As the reader suspends their personal existence to engage with the body of the book, the latter helps deliver them into life-actual, all the while internalising a story unravelling its own textual cessation. This perspective on Ulysses involves re-tracing the human body within each narrative level, and the changes it undergoes through the novel’s embeddedness.